Experimental study on spraying performance of biological pesticides in aerial rotary cage nozzle - Ru, Yu; Liu, Yangyang; Qu, Rongjia; Patel, Manoj Kumar (International Journal of Agricultural and Biological Engineering, 2020)
Aviation spraying is one of the most important methods for the treatment of forestry pests and diseases, which has a high operation efficiency and effectiveness. The combination of aviation spray and biological pesticides to reduce the impact of pesticide spray on environment has become an important development in the direction of agricultural aviation. In order to explore the effects of aviation spray parameters on particle size distribution and activity retention of biological pesticide droplets, a system of droplets size test and an activity retention rate test system of biological pesticides were constructed. The related experiments were conducted by changing the structural parameters of the rotary cage nozzle (the diameter of nozzle) and the technical parameters of the operation (rotary speed and flow). The results showed that the average relative width S of the droplets of the rotary cage nozzle was close to 1, and the droplet distribution was uniform. The influence factors on the particle size distribution of biological pesticide droplets were rotary speed, nozzle diameter, medium and flow in descending order. The rotary speed, nozzle diameter, and medium had a significant influence on droplet size distribution. The average activity retention rate of Bacillus thuringiensis was 88.83%, and the germination rate of Beauveria bassiana was 89.80%. The rotary speed had a significant effect on the activity retention rate of bacterial and fungal biological pesticides, and it was negatively correlated. The rotary speed was between 3000-5000 r/min, and the activity retention rate was higher. The research results can provide guidance for spraying biological pesticides in aerial plant protection operations with rotary cage nozzle.Keywords: forestry disease and pest control, biological pesticide, activity retention rate, aerial rotary cage nozzle, droplet distributionDOI: 10.25165/j.ijabe.20201306.5511Citation: Ru Y, Liu Y Y, Qu R J, Patel M K. Experimental study on spraying performance of biological pesticides in aerial rotary cage nozzle. Int J Agric & Biol Eng, 2020; 13(6): 1–6.